[3 + 2] cycloaddition and subsequent oxidative dehydrogenation between alkenes and diazo compounds: a simple and direct approach to pyrazoles using TBAI/TBHP. Issue 36 (19th August 2016) - Shao, Ying; Tong, Jingjing; Zhao, Yanwei; Zheng, Hao; Ma, Liang; Ma, Meihua; Wan, Xiaobing
Abstract : Herein, an efficient [3 + 2] cycloaddition and oxidative dehydrogenation reaction of diazo compounds and alkenes was well developed using TBAI/TBHP, leading to pyrazoles with moderate to high yields. Abstract : A novel Bu4 NI-catalyzed pyrazole formation reaction is well described via sequential [3 + 2] cycloaddition and oxidative dehydrogenation reactions using TBHP as the primary oxidant. In comparison with previous cases toward pyrazoles from alkenes and diazo compounds, alkenes without a pre-organized leaving group were applied in this transformation. In addition, this methodology was distinguished by its broad substrate scope, commercially available inexpensive starting materials, high atom economy and operational simplicity.